Postoperative radiotherapy with volumetric modulated arc therapy of lacrimal gland carcinoma: two case reports and literature review. (November 2014) - Orlandi, Ester; Takanen, Silvia; Giandini, Tommaso; Iannacone, Eva; Fontanella, Walter; Locati, Laura; Carrara, Mauro; Bossi, Paolo; Bergamini, Cristiana; Granata, Roberta; Tombolini, Vincenzo; Ibba, Tullio; et al.
ABSTRACT : Aims: To evaluate technical issues and clinical outcomes after postoperative volumetric-modulated arc therapy (VMAT) in two cases of malignant lacrimal gland cancer.Patients & methods: Patients were treated by postoperative VMAT and post-treatment clinical outcomes were followed-up to 18 months.Results: Dosimetric results were acceptable and acute toxicity was manageable in both patients. No evidence of disease was found at latest follow-up. One patient underwent corneal transplant for central corneal ulceration, experiencing reduction of visual acuity.Conclusion: Postoperative VMAT for treatment of lacrimal gland tumors offers improved outcome, with manageable side effects. In the context of photon beam radiotherapy, VMAT emerged as a valuable treatment option for these malignant tumors.